- Quality 4.0 in service companies (Dissertare, 2021)
Quality 4.0 is a term that emerged from industry 4.0 or the fourth industrial revolution. This is defined as the set of concepts and techniques from quality management, in which the digitalization of operations and the interaction of people are used to improve what is already there. Thus, higher yields are obtained from the processes and tasks that are already carried out in companies. The present work aims to analyze the applications of the 4.0 quality approach in the service sector, especially in the Venezuelan context, highlighting the use of digital tools as a fundamental variable to overcome the challenges of the pandemic in the current scenario. The study has a descriptive character and documentary design, supported by bibliographic review techniques, with the application of critical and content analysis. Some of the results of the study are the use of quality 4.0 digital tools in service companies of the Lara state and the improvements obtained through it. Some of the conclusions obtained are the importance of redesigning traditional service quality management approaches in companies and giving way to new business models, in which predictive and analysis in real time throughout the entire value chain contribute to elevate the customer experience and reduce the non-quality costs.
Keywords: quality 4.0; fourth industrial revolution; industry 4.0; services